2014
DOI: 10.1002/elps.201300499
|View full text |Cite
|
Sign up to set email alerts
|

Equalizer technology followed by DIGE‐based proteomics for detection of cellular proteins in artificial peritoneal dialysis effluents

Abstract: Peritoneal dialysis effluent (PDE) represents a rich pool of potential biomarkers for monitoring disease and therapy. Until now, proteomic studies have been hindered by the plasma-like composition of the PDE. Beads covered with a peptide library are a promising approach to remove high abundant proteins and concentrate the sample in one step. In this study, a novel approach for proteomic biomarker identification in PDEs consisting of a depletion and concentration step followed by 2D gel based protein quantifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Forty PDEs obtained from a prospective randomized controlled cross-over trial in 20 PD patients treated with standard or AlaGln-supplemented PD fluids were depleted and enriched using the CPLL approach previously developed in artificial PDE ( 20 ). Clinical results of a trial of this novel therapy were recently reported ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty PDEs obtained from a prospective randomized controlled cross-over trial in 20 PD patients treated with standard or AlaGln-supplemented PD fluids were depleted and enriched using the CPLL approach previously developed in artificial PDE ( 20 ). Clinical results of a trial of this novel therapy were recently reported ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…The PDE was processed immediately following the end of the dwell and aliquoted samples were stored at −80 °C until further analysis. The protocol was performed as previously reported ( 20 ) with minor adaptations for clinical samples. CPLL equalizer beads (ProteoMiner, BioRad, Hercules, CA) were prepared according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aliquots of the IPS were analyzed by 2D immunoblot as previously described [ 36 ]. The total protein pattern of the IPS was imaged on the membrane by fluorescence detection, and was used to guide alignment of immunoblot signals and 2D-DIGE quantification with the aid of the image warping capabilities of the Delta2D 4.3 software (Decodon, Greifswald, Germany).…”
Section: Saturation Labeling 2d-dige Analysismentioning
confidence: 99%
“…Recently, Lichtenauer et al have established a novel approach for proteomic biomarker identification in peritoneal dialysis effluent (PDEs) using the equalizer technology followed by 2D-DIGE [37]. The experimental approach was proven using a model system for PDE that is further referred to as artificial PDE, which was established by spiking unused peritoneal dialysis fluids with cellular proteins reflecting control conditions or cell stress.…”
Section: Protein Equalizer Technologymentioning
confidence: 99%